A (in) disponibilidade dos direitos fundamentais trabalhistas : a figura do distrato como modo de cessação do contrato de emprego - Hainzenreder Júnior, Eugênio (2016)
This research focuses on the issue of (non) availability and (non) waiver of fundamental labor rights of art. 7 of CF / 88, in order to examine the possibility of the parties to dispose these rights through consensual termination of the employment relationship by a termination agreement. Although the forms of employment contract termination are often subject of investigation by the doctrine, the termination of the employment relationship through an terminating agreement is subject rarely addressed in labor harvest, considering the restriction of the autonomy of the will of the parties based on the principle of unavailability and non-waiver of rights. The labor law doctrine, excepting the hypothesis of volunteer dismissal programs, which occur, as a rule in the midst of collective bargaining, holds inexistence practical application of such contract termination mode, as Articles 9, 444 and 468 of the Labor Cod, would hinder it. The research therefore initially depurates the foundations of unavailability elicited from the doctrine, jurisprudence and labor laws in seeking to outline a concept of available rights. Thus, the study aims, on the one hand, not to overlook the undeniable social interest which covers labor law and, at the same time, rule out the existence of absolute rights to annihilate a minimum of conformation space of autonomy of the will of the parties in the context of the employment contract. Overcome this issue and established assumptions about the (non) availability of labor rights and its limitations and presuppositions, the research examines whether employee and employer may waive or transact rights through consensual termination of the employment contract. Therefore, this research aims to withdraw the absolute presumption of vitiated consent on which the act of disposal is prohibited and recognize the private autonomy of the parties considering: a) the ascertaining of the validity of the employee's consent; b) its interpretation by objective good faith and “venire contra factum proprium”; c) and the existence of a general right to freedom and the principle of human dignity in its autonomy dimension, without disregarding the necessary dialogue with its heteronomous dimension.